Design and analysis a new simple tire nut opener - Mohd Hasrul Naim, Md. Rahim (2009)
Tire nut removal is a tool and gadget to help the user to loosen and tight the tire nut. This project was carried out to improve and optimize the tire nut removal for wheel with Pitch Cycle Diameter (PCD) 114.4 mm such as Proton Waja, Proton Saga, Kia Careens, and Hyundai Sonata. In this academic project, the main objective was to improve the tire nuts removal in term of size, weight, efficiency and flexibility. The tire nut removal prototype had been involved design, design calculation, analysis, simulation approach and material selection. The project applies the consideration a failure analysis of the structure analysis. In fact, the spur gear was one most important redesign part for this project to minimize the human involvement and make the car tire removal process easier and flexible. This flexible tire nut removal allows the user to operate it in the situation with or without electricity supply from the car cigarette lighter plug. Because the user could disassembly the motor casing by easily when want to operate it manually. The new gadget could help the user to change tire by easily lower the torque that requite to remove tire nut. So this tool able to reduce the torque requires removing tire nut until 162 times lower than original torque.